Efeito agudo do alongamento estático no desempenho neuromuscular de idosas : comparação entre membros - Gonçalves, Raquel (Universidade Federal de São Carlos, 2016)
The aim of the present study was to analyze the acute effects of static stretching on isometric peak torque (PT), electromyographic (EMG), maximum range of motion (ROM), peak passive torque and maximum angle passive torque of elderly, in upper and lower limbs. The sample consisted of 15 women (67.0 ± 4.0 years old; 70.0 ± 12.0 kg, 1.56 ± 0.0 m; 28.6 ± 5.0 kg / m2). Isometric PT and EMG activity of the biceps brachii (BB) and biceps femoris (BF) were tested in two exercises (elbow flexion or knee flexion), after two separate conditions: stretching (S) (3 sets of 30 seconds) and control (C). Maximum ROM, peak passive peak torque and maximum angle passive torque were evaluated using an isokinetic dynamometer after the conditions S or C. Each day, only one condition and a type of exercise were tested and order employment for each condition and exercise were determined randomly. Three post-conditions were made to observe the behavior of force, muscle activity and ROM. The two-way ANOVA showed significant exercise interaction vs. condition (p = 0.01) to isometric PT, and the stretching caused significant decreases in isometric PT values for the knee flexors (8%) and no change was observed in the elbow flexors isometric PT values. There was no significant exercise interaction vs. condition (p = 0:14) to EMG for the BB and BF muscles. In addition, the paired t-test showed that the stretching protocol caused significant increase in the maximum ROM (p = 0.01), but the peak torque and maximum angle passive torque remained unchanged. In conclusion, acute series of static stretching may affect the ability of the knee flexors to produce maximum muscle strength, but do not affect the performance of the elbow flexors. Further, three series of 30-second static stretching increases the knee flexors maximum ROM, but do not alter the peak torque and maximum angle passive torque of elderly women.
Keywords: Alongamento; Força muscular; Envelhecimento; Stretching; Muscular strength; Aging; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL